2002
DOI: 10.1023/a:1021851230890
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory screening of the medicinal plant Gynura procumbens

Abstract: Gynura procumbens is used in Thai folk medicine to treat topical inflammation, rheumatism, and viral ailments. In the present work, attempts were made to verify the folk medicinal claim that the crude ethanolic extract of G. procumbens has antiinflammatory action and to relate the activity to particular fractions using a croton oil-induced mouse ear inflammation model. The original ethanolic extract of G. procumbens was partitioned between water and ethyl acetate. The residues were subjected to antiinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 2 publications
0
58
0
Order By: Relevance
“…Studies showed its activity against cancer, inflammation, diabetes and viral infections (Akowuah et al, 2002;Iskander et al, 2002). Antiulcer activity of ethanolic leaf extract of G. procumbens was evaluated in rats against ethanol induced gastric ulcerative lesions.…”
Section: Gynura Procumbensmentioning
confidence: 99%
“…Studies showed its activity against cancer, inflammation, diabetes and viral infections (Akowuah et al, 2002;Iskander et al, 2002). Antiulcer activity of ethanolic leaf extract of G. procumbens was evaluated in rats against ethanol induced gastric ulcerative lesions.…”
Section: Gynura Procumbensmentioning
confidence: 99%
“…It has been extensively used as a traditional herbal medicine particularly in South East Asia. The plant is used for the treatment of many different ailments such as rash, kidney diseases, eruptive fever, hemorrhoids, and inflammation (Perry and Metzger 1980;Iskander et al 2002). The leaf of G. procumbens is not toxic (Rosidah et al 2009) and it has been used in folk medicine to control the blood sugar level of diabetic patients (Akowuah et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Jiratchariyakul et al (2000) reported that the plant extracts have anti-replicative action against herpes simplex virus and identified 3,5-di-O-caffeoylquinic acid and 4,5-di-O-caffeoylquinic acid as the active components. Moreover, the leaf or aerial parts of G. procumbens showed an anti-inflammatory (Iskander et al 2002) and antihypertensive (Hoe et al 2007) activity but the chemical properties as regard to the respective activities need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…(Asteracea) is a medicinal plant used in South East Asia for treating various ailments such as hemorrhoids, inflammation, diabetes, etc. (Perry and Metzger 1980;Iskander et al 2002). The leaf is used in folk medicine to control the blood sugar level of diabetic patient.…”
Section: Gynura Procumbens Lourmentioning
confidence: 99%